Ramalan Zodiak dalam Pandangan Islam: Studi Takhrij dan Syarah Hadis - Cut Shabrina Dzati Amani; Hidayatul Fikra; Ayi Rahman; Dian Siti Nurjana (Gunung Djati Conference Series, 2022)
This research aims to discuss the hadith about the prohibition of studying tanjim science with regard to the trend of society in believing in the zodiac. The method used in this research is a qualitative method with an emphasis on the study of literature studies through takhrij method and hadith sharah. The result of this study is the discovery of the status of hadith quality regarding the prohibition of studying tanjim science, namely shahih. Also this hadith includes the hadith that maqbul (accepted) so it is mandatory to practice. The conclusion of this study is to study, believe and practice the zodiac is the application of the concept of tanjim science, where the law is haram because it includes shirk. This research recommends continued research with collaboration between academics of hadith science, jurispruding, and social sciences so that proper prevention efforts are generated so as not to easily trust the zodiac among the public.